Redescription of Acanthicus hystrix Agassiz, 1829 (Siluriformes: Loricariidae), with comments on the systematics and distribution of the genus - Chamon, Carine C. (Zootaxa, 2016)
The genus Acanthicus is diagnosed from remaining Loricariidae genera by several characters, including the absence of adipose fin, pectoral-fin spine enlarged and the presence of small plates in abdomen region. Acanthicus currently comprises two valid species: A. hystrix and A. adonis. Acanthicus hystrix is distinguished from A. adonis, mostly by having body and fins dark brown to almost completely black background colored, without clear spots or dots (vs. dark brown color background with white spots covering body and fins) and presence of ochre to grey stripes in caudal fin (vs. stripes absent on caudal fin). The holotype of A. hystrix was destroyed during a bombing raid in the Second World War, no neotype was designed and the species is recognized by the illustration present in the original description, whose text is short, and uninformative. In the present contribution, specimens from several institutions were examined, revealing that the species is widespread in the Amazon, Tocantins-Araguaia and Orinoco basins, while A. adonis is restricted to the lower rio Tocantins. Herein, a redescription of Acanthicus hystrix is provided, with a comprehensive diagnosis of the genus and its species, along with a distribution map of the genus, a key to species identification, and brief comments on the systematics and distribution of the genus.